Uncommon fungal infection in a renal transplant recipient: A case report from Northern India (Indian Journal of Case Reports, 2026)
Although fungal infections can occur, their reported incidence in India is significantly lower than that of other infections, making them uncommon findings in renal transplant patients. Here, we present an unusual case of a fungal infection that developed in a 32-year-old Indian male renal transplant recipient. After correlating clinical, microbiological, and histopathological findings, a final diagnosis of fungal infection was established. The patient responded well to anti-fungal medications. This case report highlights that though tuberculosis is the most commonly observed infection in the Indian scenario, the occurrence of a fungal infection is an unusual finding in post-renal transplant cases, thus posing a massive diagnostic and therapeutic challenge. Their prompt diagnosis is imperative for the patient’s survival.